2022
DOI: 10.31763/ijrcs.v2i3.798
|View full text |Cite
|
Sign up to set email alerts
|

NB Theory with Bargaining Problem: A New Theory

Abstract: A new theory is proposed to achieve desired set of values for an engineering system based on a single algorithm that consists of all optimization algorithms. This algorithm considers an engineering system's main variables, dimensions, and functions; all these parameters will be set and tuned by a systematic search in the main library. This single algorithm automatically selects an optimization algorithm suitable for a particular optimization problem. Additionally, this theory, which was inspired by the idea of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The single-photon QKD explore utilizing quantum spots by Waks et al [18] acknowledged at an activity frequency of 877nm revealed the biggest secure key rate to date. Crafted by Leifgen et al [19] addresses the current stateof-the craftsmanship for QKD executions with variety focuses on jewel.…”
Section: -Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The single-photon QKD explore utilizing quantum spots by Waks et al [18] acknowledged at an activity frequency of 877nm revealed the biggest secure key rate to date. Crafted by Leifgen et al [19] addresses the current stateof-the craftsmanship for QKD executions with variety focuses on jewel.…”
Section: -Discussionmentioning
confidence: 99%
“…Out ow of one photon excitons caught by molecularly dainty gems Initially, it was restricted to WSe2 monolayers [12][13][14][15][16]. Then, at that point, utilizing WS2 [17], MoS2 [18,19] was lled and MoTe2 [20].…”
Section: -Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluate the effect of receive diversity on the error performance of the code using MATLAB Software [30][31][32][33][34][35][36]. Performance is calculated by using 2 transmit antennas and different number of receive antennas for Rayleigh fading channel.…”
Section: -Simulation Resultsmentioning
confidence: 99%
“…This new symbol 𝑡𝑟𝑒𝑙𝑙𝑖𝑠 1 has the same number of states and a length of N = NC/Q steps (see Figure 3). As the code structure has not been broken by an interleaver only 2 𝑅𝑄 transitions have to be considered for each state instead of 2 𝑄 [30][31][32][33][34][35][36].…”
Section: -Viterbi Algorithm For Sttcmentioning
confidence: 99%